PAI LEARNING INNOVATIONS THROUGH THE STRENGTHENING OF THE PANCASILA STUDENT PROFILE AND THE STUDENT PROFILE OF RAHMATAN LIL ALAMIN (P5PPRA) - Jannah, Nurul; Anam, Nurul (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
This study aims to examine innovations in Islamic Religious Education (PAI) learning through the reinforcement of P5PPRA at MIMA 01 KH. Shiddiq Jember. In this context, P5PPRA functions not only as a platform for character building based on Pancasilavalues but also as a means of instilling moderate Islamic values such as tasamuh (tolerance), global-mindedness, tatawwur wa ibtikar (dynamism and innovation), ta’adub (civility), and qudwah (exemplary conduct). The learning process is carriedout through the integration of project-based activities that emphasize collaboration, social awareness, and the habituation of noble character in students' real-life experiences. The research method used is a qualitative approach with a case studydesign. The results show that PAI learning innovation through the reinforcement of P5PPRA at MIMA KH. Shiddiq is implemented systematically through three stages: planning, implementation, and evaluation. The planning stage is integrated into PAIsubjects using structured teaching modules that include learning objectives, activity flow, and assessments based on the values of Pancasila and Islam Rahmatan Lil Alamin. The implementation involves various methods, including discussions and hands-on practice, emphasizing cooperation, responsibility, and exemplary behavior. Evaluation is holistic, assessing knowledge, skills, and attitudes. Teachers play an active role in character development and provide guidance for students who have not yet achieved the minimum learning mastery